PENGEMBANGAN E-HANDOUT BERBASIS PLATFORM CANVA PADA MATERI BUMBU DASAR DAN REMPAH UNTUK SMK KULINER FASE E - Luna Rizky Nurmala; Sri Handajani; Ita Fatkhur, Romadhoni; Ratna Palupi Nurfatimah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
E-handouts are one of the instructional materials used to facilitate the learning process. This study aims to determine: 1) the development of an e-handout using the Canva application, 2) the feasibility of the content and media, and 3) students' responses to the e-handout on the topic of basic seasonings and spices. This development research employed the ADDIE model, limited to the third stage (Development). The assessment instruments used to collect data on content, teaching media, and student responses used a four-point Likert scale. Validation of the content and media was carried out by three validators each, while student responses were assessed by 34 students of Phase E (Grade X) Culinary Program at SMKN 1 Dlanggu, Mojokerto. Data were analyzed using descriptive percentage analysis. The results show that: 1) the e-handout was developed in accordance with the ADDIE model procedures up to the Development stage; 2) the content and media of the e-handout were rated highly feasible, with average scores of 3.57 (89.46%) and 3.68 (92.13%) respectively; and 3) student responses were also very good, with an average score of 3.48 (87.18%). This study produced an e-handout that is ready to be implemented in classroom learning.